The role of financial knowledge in realizing financial behavior: is it any mediating effect of financial attitudes and self-efficacy? - Maulida H, Ardiana Nur; Indarto, Indarto; Santoso, Aprih (Asian Management and Business Review, 2021)
The purpose of the study was to analyze the effect of financial knowledge on financial behavior with financial attitudes and self-efficacy as mediating variables. The population of this research is that all students in Semarang are unknown. The number of respondents to 96 people. The sample selection method is purposive sampling, namely: students have taken courses in financial management and intermediate financial accounting and the analytical tool used in this study was Warp PLS version 5.0. The results showed that financial knowledge has a positive and significant direct effect on financial attitudes, self-efficacy and financial behavior of students in Semarang City, so that the proposed hypothesis can be accepted. Financial attitudes and self-efficacy have a positive and significant direct effect on the financial behavior of students in Semarang City, so that the proposed hypothesis can be accepted. Financial attitudes and self-efficacy do not mediate the effect of financial knowledge on financial behavior of students in Semarang City.